2020
DOI: 10.1186/s41927-020-00146-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient insights on living with idiopathic inflammatory myopathy and the limitations of disease activity measurement methods – a qualitative study

Abstract: Background The idiopathic inflammatory myopathies (IIMs) are chronic autoimmune conditions, typically resulting in proximal muscle weakness and impacting upon quality of life. Accurate measurement of IIM disease activity is imperative for appropriate medical management and carrying out valid clinical trials. The International Myositis Assessment and Clinical Studies Group (IMACS) “Disease Activity Core Set Measures” are the current gold-standard of IIM disease activity assessment. Anecdotally, patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…All forms of myositis significantly impact the quality of life of those who are diagnosed, as they present with a broad range of debilitating symptoms requiring ongoing medical treatment. People with myositis report pain, fatigue, and day-to-day fluctuation of symptoms as being the most impactful symptoms [ 47 49 ]. Research examining people’s experiences with multiple sclerosis has found that delays in diagnosis may create a sense of uncertainty and, in many cases, a worsening of symptoms, leaving people in a state of ‘not knowing’ [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…All forms of myositis significantly impact the quality of life of those who are diagnosed, as they present with a broad range of debilitating symptoms requiring ongoing medical treatment. People with myositis report pain, fatigue, and day-to-day fluctuation of symptoms as being the most impactful symptoms [ 47 49 ]. Research examining people’s experiences with multiple sclerosis has found that delays in diagnosis may create a sense of uncertainty and, in many cases, a worsening of symptoms, leaving people in a state of ‘not knowing’ [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shorter activities, such as dressing, are usually more tolerated. It is not uncommon that patients cope with fatigue by tailoring their tasks to reduce the duration of exertion, limiting travel and planning rest periods after demanding activities (7).…”
Section: Fatigue In Inflammatory Myopathies: Clinical Aspects and Phy...mentioning
confidence: 99%
“…Despite being a common symptom in myositis, fatigue is not routinely assessed during medical examinations, probably due to a poor awareness of it from both patients and clinicians (7). This is also a reason why there is paucity of validated, IMMs-specific scales to measure fatigue, although different methods and scales have been proposed.…”
Section: Diagnosing and Measuring Fatigue In Iimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative research indicates IIM flares are characterized by brief (i.e. 2–3-day) acute increases in symptom severity, including myalgia, weakness, and fatigue, compared with a baseline over recent days [ 12 ]. Daily patient-reported symptom data could potentially allow objective identification of such symptom-based flares using an a priori definition, similar to that of Parry et al in OA [ 3 ].…”
Section: Introductionmentioning
confidence: 99%